Enzymatic approaches to nicotinic acid synthesis: recent advances and future prospects - Singh, Rahul Vikram; Kalia, Vipin Chandra; Sambyal, Krishika; Singh, Bakul; Kumar, Anurag; Lee, Jung-Kul (Frontiers in Bioengineering and Biotechnology, 2025)
Biocatalyst-mediated reactions have led to revolutionary transformations in the organic synthesis of pharmaceuticals, drugs, and other chemicals. Nicotinic acid (vitamin B3) is an essential precursor for nicotinamide adenine dinucleotide (NAD+) biosynthesis and is vital for numerous metabolic processes. Since the human body cannot synthesize nicotinic acid, it relies on external sources. Therefore, nicotinic acid synthesis has gained huge attraction. In recent years, the industrial production of nicotinic acid has increasingly shifted from traditional chemical methods to more biocatalytic processes, leveraging the power of biocatalysts. This review highlights the biocatalyst-mediated synthesis of nicotinic-acid- and nitrile-metabolizing enzymes through state-of-the-art omics-based techniques to improve enzyme catalytic efficiency and stability via various approaches. Future research prospects and challenges associated with nicotinic acid production are also discussed.